Chemical constitution of a Permian-Triassic disaster species - Sephton,MA; Visscher,H; Looy,CV; Verchovsky,AB; Watson,JS (GEOLOGY, 2009)
One of the most controversial biological proxies of environmental crisis at the close of the Permian is the organic microfossil Reduviasporonites. The proliferation of this disaster species coincides with the mass extinction and numerous geochemical disturbances. Originally Reduviasporonites was assigned to fungi, opportunistically exploiting dying end-Permian forests, but subsequentgeochemical data have been used to suggest an algal origin. We have used high-sensitivity equipment, partly designed to detect interstellar grains in meteorites, to reexamine the geochemical signature of Reduviasporonites. Organic chemistry, carbon and nitrogen isotopes, and carbon/nitrogen ratios are consistent with a fungal origin. The use of this microfossil as a marker of terrestrial ecosystem collapse should not be merely discounted. Unequivocally diagnostic data, however, may have been precluded by post-burial replacement of its organic constituents.